Midface Infection after COVID-19 Vaccination in a Patient with Calcium Hydroxylapatite Dermal Filler: A Case Report and Literature Review - Jeon, Hong Bae; Yoon, Jae Hee; Lim, Nam Kyu (Archives of Plastic Surgery, 2022)
The emergence of vaccines for coronavirus disease 2019 (COVID-19) raises risk of possible adverse events from interaction between the vaccines and facial aesthetic care. A 47-year-old female with no medical comorbidities visited our emergency room due to midface painful swelling after 3 hours following receiving the second dose of the messenger RNA BNT162b2 COVID-19 vaccine. About 14 years ago, she underwent nonsurgical augmentation on the nasojugal groove with a calcium hydroxylapatite dermal filler. We performed incision and drainage under general anesthesia on the next day. During operation, yellowish pus-like materials bulged out. After an operation, we performed a combination therapy with antibiotics and methylprednisolone. Her symptoms improved day by day after surgery, and then a complete recovery was achieved at 3 weeks after the treatment. In conclusion, providers of aesthetic procedures are to be aware of the potential risks of such vaccines for patients who already had or seek to receive dermal filler injections.
Keywords: COVID-19 vaccine; dermal filler; inflammation